To ask or not to ask? Investigating workers' flexibility requests and the phenomenon of discontented non-requesters. (2nd April 2016) - Skinner, Natalie; Cathcart, Abby; Pocock, Barbara
ABSTRACT: Flexible working arrangements have attracted growing attention in workplaces across Australia and in many other countries in recent years. This contribution utilises the results of two large Australian employee surveys to analyse who asks for flexibility, why, and with what effects on work-life interference. This analysis is set in the context of Australia's 'Right to Request' (RTR) provisions which, at the time of the study, gave parents of preschool children and those with a disabled child aged up to 18 the RTR flexibility. The analysis also draws on a set of qualitative interviews of those we term 'discontented non-requesters' (that is, those who are not content with current arrangements but who do not ask for flexibility) to probe beneath the survey results to consider explanations about why some people do not ask for flexibility despite desiring different working arrangements. We conclude with the implications for policy and regulation.